Case Study Research on Nurses’ Perceptions of Various Educational Strategies for Learning Perioperative Non-technical Skills - Clendinneng, Debra (Operating Room Nurses Association of Canada Journal, 2020)
Operating rooms are complex interprofessional environments. Nurses must ensure patient safety through effective, advanced, communication and teamwork skills, task management expertise, and focused awareness of all intraoperative activity as situations evolve. This research explores the gap in the literature about what educational strategies nurses perceive to be effective in learning non-technical skills (NTS) within current college hybrid programs. Results contribute to perioperative education and the teaching of NTS.